PENYULUHAN KONSERVASI LINGKUNGAN BERBASIS AL QUR’AN: (Living Qur’an dan Penguatan Nilai-Nilai Qur’ani Pada Masyarakat Sembalun Bumbung Terhadap Ayat-Ayat Ekologi dan Konservasi) - Said, Muhammad; Yunus, Muhammad; Rahman, Abd.; Asiah, Siti; Tahir, Muh. Tarmizi; Paizin, Khaerul; Wulandari, Suci (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2023)
This article discusses Qur'an-based environmental conservation counseling and strengthening Qur'anic values on ecology and conservation verses in Sembalun Bumbung, East Lombok, West Nusa Tenggra. The purpose of this activity is to raise public awareness of the importance of preserving the environment and provide an understanding of how the Qur'an provides guidance in protecting nature. The methods used in this extension activity are lectures and group discussions. The results showed that this activity succeeded in increasing people's knowledge and awareness about the importance of environmental conservation and encouraging them to implement Qur'anic values in their daily lives to preserve the environment. Keywords: extension, conservation, ecological verse, qur;anic value.